Alturas residenciales : La segunda Escuela de Chicago - Fernandez-Galiano, Luis (AV, 2001)
Análisis de cinco obras de Mies: Promontory, 860-880 Lake Shore Drive, 900 Esplanade, Commonwealth Promenade, Lafayette Park